STUDY ON COASTAL HYDRODYNAMIC REGIME IN THE MEKONG RIVER MOUTH AREA - Tiến, Nguyễn Ngọc (Vietnam Journal of Marine Science and Technology, 2014)
This study shows some results of computed hydrodynamic processes by using MIKE 21/3 COUPLE model, including hydrodynamic (HD), spectral wave (SW) modules. The outputs are waves, currents and water levels fluctuation in storms and monsoon conditions. The study results represent the hydrodynamic processes in Mekong River mouth area under the impact of land-sea interaction processes. These results are helpful to find out the mechanism of accretion, erosion, sedimentation processes in study region. It may serve as the good information for planning and proposing the suitable training measures for socio-economic sustainable development.